Energy performance analysis of a suspended backpack with an optimally controlled variable damper for human load carriage. (April 2020) - Yang, Lianxin; Zhang, Jiwen; Xu, Yuning; Chen, Ken; Fu, Chenglong
Highlights: We study the energetics of load carriage with a variable damped suspended backpack. Optimal control is designed for the variable damper to maximize walking economy. An event-based optimal control strategy is proposed to improve the adaptability. The semi-active control improves energy efficiency and reduces peak load force. The working principle of the system is also analyzed theoretically. Abstract: This paper investigates the energy performance of human load carriage with a variable damped suspended backpack. A vertical double-mass coupled-oscillator model is adopted to predict the load movement and energy consumption. Optimal control is found to be bang-bang, switching four times between the minimum and the maximum damping in a step cycle. With analytically tested laws for optimal switching timing, an orbitally stable event-based control strategy with feedback is designed. Simulation results reveal that the suspended backpack with an optimally controlled variable damper improves the energy efficiency of load carriage and reduces the load force exerting on carriers for a wide range of suspension stiffness and walking conditions, representing less energy expenditure, better comfort and stronger adaptability over the passive elastic backpacks with constant suspension parameters. The working principle of the variable damper is also analyzed. Although this paper only deals with the theoretical model and analysis of the problem, the discussion on validity implies a considerable improvement in energy performance, including efficiency and adaptability.